Distal Fibula Osteotomies Improve Tibiotalar Joint Compression: A Cadaveric Study. Issue 3 (14th September 2018) - Arena, Christopher; Aydogan, Umur; Roush, Evan; Juliano, Paul
Category: Basic Sciences/Biologics Introduction/Purpose: Compression is a vital component of achieving a successful ankle arthrodesis. Various modifications of the fibula are used in hopes of achieving higher clinical rates of successful fusion in ankle arthrodesis procedures. We hypothesized that distal fibula osteotomies would improve tibiotalar joint compression under various loading conditions. The purpose of this study was to evaluate the effect of various distal fibula osteotomies on tibiotalar joint compression. Methods: Eight paired adult cadaveric lower extremity specimens with an intact ankle joint and syndesmosis were prepared by exposing and fixating together the proximal tibia and fibula. A jig was constructed to secure the specimen in a vertical position while allowing free axial loading. An anterior surgical approach to the ankle was performed and the joint cartilage denuded. A pressure transducer was used to record baseline ankle pressure distribution. The proximal specimen was loaded with 30, 50, and 100 N static weight and ankle pressure measurements repeated for each load. The fibula was surgically modified with the three procedures: (1) oblique fibular osteotomy 3 cm proximal to the ankle joint; (2) 1 cm long distal fibula resection; (3) complete distal fibula excision. Increasing loads of 30, 50, and 100 N following each surgical procedure were applied and the ankle pressure measurements repeated. Results: Distal fibula resection increased tibiotalar joint force, peak pressure, and contact area compared to intact fibula control for 30, 50, and 100 N loads applied (p<0.05). Compared to intact fibula control, an oblique osteotomy performed and 30 N applied force resulted in a mean ankle joint force increase of 7.5 N (p = 0.007). A 1 cm excisional fibula osteotomy under a 30 N load significantly increased the ankle joint force by 6.6 N (p = 0.015). Complete distal fibula resection under 30 N load significantly increased the ankle joint force compared to control by 13.9 N (p < 0.001). Similar trends were seen for 50 N and 100 N loads with significance reached (*) as represented in Figure 1 (error bar = standard error). Conclusion: A distal fibula oblique osteotomy, 1 cm excisional osteotomy, or complete distal fibula excision may increase the amount of force transmitted to the ankle joint under loading. Our findings suggest complete distal fibular resection results in the highest ankle joint force, contact area, and peak pressure of the surgical options tested. Leaving the fibula intact may decrease tibiotalar compression during ankle arthrodesis. Clinical testing would be important to ultimately test the effects on rates of successful fusion.